Development and application of a predictive model of riverine fish community assemblages in the Taranaki region of the North Island, New Zealand - Michael K. Joy; Russell G. Death (New Zealand Journal of Marine and Freshwater Research, 2000)
A predictive model of fish community composition using a reference condition approach is proposed for the Taranaki region of New Zealand. The model is used to quantify the effects of barriers on the migration of native fish in the region. Occurrence records of fish in streams without migratory barriers (reference sites) obtained from the New Zealand freshwater fish database were used to establish trajectories of occurrence for each of 12 fish species with altitude. The relative occurrence per site for each of the species was calculated and used as the probability of the presence of that species in that altitudinal range. Comparison of these probabilities with the fauna actually found at a test site expressed as an observed over predicted ratio (O/P) is then used to compare sites to quantify barrier effects on fish communities. In a similar way this process can be used to monitor the effectiveness of fish passes, where present on dams. Independent data from 85 sites sampled over the summer of 1997/98 were used to test the predictive model. As an example of a typical use of the methodology, the effect of a single hydrodam on fish communities is illustrated.